Short and long-term trajectories of the post COVID-19 condition: Results from the EuCARE POSTCOVID study - Andrea Santoro; Francesca Bai; Maria Francesca Greco; Roberta Rovito; Matteo Sala; Lidia Borghi; Kyrie Piscopo; Elena Vegni; Julia Fonseca de Morais Caporali; Carolina Coimbra Marinho; Arnaldo Santos Leite; Maria Mercedes Santoro; et al. (BMC Infectious Diseases)
Abstract Background Post COVID-19 condition (PCC) affects 10–40% of patients and is characterized by persisting symptoms at ≥ 4 weeks after SARS-CoV-2 infection. Symptoms can last 7 or even more months. How long PCC persists and any changes in its clinical phenotypes over time require further investigation. We investigated PCC trajectories and factors associated with PCC persistence. Material and methods We included both hospitalized COVID-19 patients and outpatients from February 2020 to June 2023, who underwent at least one follow-up visit after acute infection at San Paolo Hospital, University of Milan. Follow-up visits were conducted at the post COVID-19 clinic or via telemedicine. During each follow-up examination, patients completed a short version of the World Health Organization (WHO) Case Report Form (CRF) for ongoing symptoms, the Hospital Anxiety and Depression Scale (HADS), and a screening tool for Post-Traumatic Stress Disorder (PTSD). Statistical analyses involved Chi-square, Mann–Whitney, Kruskal–Wallis tests, and logistic regression analysis. Results We enrolled 853 patients (median age 62, IQR 52–73; 41% females). 551/853 (64.6%), 152/418 (36.4%) and 21/69 (30.4%) presented PCC at median follow up of 3 (IQR 2–3), 7 (IQR 6–10) and 26 (IQR 20–33) months, respectively (p < 0.001). The main clinical phenotypes were fatigue, respiratory sequelae, brain fog and chronic pain; anosmia/dysgeusia was observed mostly in the first post-acute period. Female sex, acute disease in 2020, a longer hospital stay and no COVID-19 vaccination were associated with persistence or resolution of PCC compared to never having had PCC. Anxiety, depression and PTSD were more common in PCC patients. By fitting a logistic regression analysis, acute infection in 2020 remained independently associated with persistent PCC, adjusting for age, sex, preexisting comorbidities and disease severity (AOR 0.479 for 2021 vs 2020, 95%CI 0.253–0.908, p = 0.024; AOR 0.771 for 2022 vs 2020, 95%CI 0.259–2.297, p = 0.641; AOR 0.086 for 2023 vs 2020, 95%CI 0.086–3.830, p = 0.565). Conclusions There was a reduction in the PCC burden 7 months following the acute phase; still, one third of patients experienced long-lasting symptoms. The main clinical presentations of PCC remain fatigue, respiratory symptoms, brain fog, and chronic pain. Having had SARS-CoV-2 infection during the first pandemic phases appears to be associated with persistent PCC.